Impact of the partnership between Japanese Society of Gastroenterological Surgery, Society of Surgical Oncology, and Annals of Surgical Oncology. Issue 4 (18th May 2019) - McMasters, Kelly M.
Abstract: The Society of Surgical Oncology (SSO) and its official journal, Annals of Surgical Oncology, have had a very important and successful partnership with the Japanese Society of Gastroenterological Surgery (JSGS). This partnership has advanced our missions of promoting high‐quality surgical science focused on improving patient outcomes. Abstract : The Society of Surgical Oncology (SSO) and its official journal, Annals of Surgical Oncology, have had a very important and successful partnership with the Japanese Society of Gastroenterological Surgery (JSGS). This partnership has advanced our missions of promoting high‐quality surgical science focused on improving patient outcomes.